Single-cell transcriptomics reveals the cell fate transitions of human dopaminergic progenitors derived from hESCs - Lingmin Liang; Yao Tian; Lin Feng; Chaoqun Wang; Guihai Feng; Glyn Nigel Stacey; Ng Shyh-Chang; Jun Wu; Baoyang Hu; Wei Li; Jie Hao; Liu Wang; et al. (Stem Cell Research & Therapy, 2022)
Abstract Background Midbrain dopaminergic (DA) progenitors derived from human pluripotent stem cells are considered to be a promising treatment for Parkinson’s disease (PD). However, the differentiation process produces undesired cell types, which influence the in vivo evaluation of DA cells. In this paper, we analyze the cell fate choice during differentiation and provide valuable information on cell preparation. Methods Human embryonic stem cells were differentiated into DA progenitors. We applied single-cell RNA sequencing (scRNA-seq) of the differentiation cells at different time points and investigated the gene expression profiles. Based on the differentially expressed genes between DA and non-DA cells, we investigated the impact of LGI1 (DA enriched) overexpression on DA differentiation and the enrichment effect of CD99 (non-DA enriched) sorting. Results Transcriptome analyses revealed the DA differentiation trajectory as well as non-DA populations and three key lineage branch points. Using genetic gain- and loss-of-function approaches, we found that overexpression of LGI1, which is specific to EN1+ early DA progenitors, can promote the generation of TH+ neurons. We also found that choroid plexus epithelial cells and DA progenitors are major components of the final product (day 25), and CD99 was a specific surface marker of choroid plexus epithelial cells. Sorting of CD99− cells eliminated major contaminant cells and improved the purity of DA progenitors. Conclusions Our study provides the single-cell transcriptional landscape of in vitro DA differentiation, which can guide future improvements in DA preparation and quality control for PD cell therapy.